Sea ports and sea power : African maritime cultural landscapes - Harris, Lynn (Springer, 2017)
This volume represents a more Africanist approach to the framework of maritime landscapes and challenges of adapting international heritage policy such as the UNESCO convention. While the concept of a maritime landscape is very broad, a more focused thematic strategy draws together a number of case studies in South Africa, Namibia, Tanzania, and Nigeria with a common thread. Specifically, the contributors address the sub-theme of sea ports and sea power as part of understanding the African maritime landscape. Sea ports and surrounds are dynamic centers of maritime culture supporting a rich diversity of cultural groups and economic activities. Strategic locations along the African coastline have associations with indigenous maritime communities and trade centers, colonial power struggles and skirmishes, establishment of naval bases and operations, and World War I and II engagements.
Keywords: Underwater archaeology -- Africa.; Africa.; elektronické knihy; electronic books